Proceedings of the DESIGN 2018 15th International Design Conference 2018
DOI: 10.21278/idc.2018.0330
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Bioinspired Approach for the Design of Kinematic Chains

Abstract: In recent years, bioinspired lightweight design has become a high priority in technology. An important source is the musculoskeletal system, which achieves a light construction by the interplay of different effects, which have the aim of minimizing bending stresses. In this paper the potentials for technology and the challenges for a transfer are discussed using kinematic chains as an example. An iterative approach is presented, which represents a solution to integrate the simultaneous optimization process of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 11 publications
0
15
0
Order By: Relevance
“…So far, tension chording is investigated for structures loaded with one-dimensional bending. In prior studies, technical lightweight design potentials of tension chording for this load case were shown (Bartz et al, 2018a;Bartz et al, 2018b;Bartz et al, 2019). Possible areas of application for tension chording are presented in a prior study (Uttich et al, 2019), but systems in the identified application scenarios are subject to more loads but bending, e.g.…”
Section: Introductionmentioning
confidence: 94%
“…So far, tension chording is investigated for structures loaded with one-dimensional bending. In prior studies, technical lightweight design potentials of tension chording for this load case were shown (Bartz et al, 2018a;Bartz et al, 2018b;Bartz et al, 2019). Possible areas of application for tension chording are presented in a prior study (Uttich et al, 2019), but systems in the identified application scenarios are subject to more loads but bending, e.g.…”
Section: Introductionmentioning
confidence: 94%
“…The human musculoskeletal system contains several subsystems with interdepending lightweight design solutions [8]. One part of the system is the human arm.…”
Section: Tension Chording Principlementioning
confidence: 99%
“…In other publications, the tension chording principle is described as a principle to reduce bending in structures by using redundant muscle and tendon forces [8,5]. We introduce a refined definition in this paper.…”
Section: Tension Chording Principlementioning
confidence: 99%
“…
Figure 9.Flow chart of the design calculation: Classical approach (left) with extensions of the bioinspired approach (right) (adjusted according to Bartz et al. 2018 a ; Bartz et al. 2018 b and Bartz 2019).
…”
Section: Practical Studies By Application On An Articulated Arm Robotmentioning
confidence: 99%